German Environmental Survey IV: environmental tobacco smoke exposure of German children. (27th October 2008) - Conrad, Andre; Seiwert, Margarete; Schulz, Christine; Becker, Kerstin; Ullrich, Detlef; Kolossa-Gehring, Marike
As the current extent of Environmental Tobacco Smoke (ETS) exposure of children in Germany is unknown, it was investigated in the German Environmental Survey (GerES IV) for Children from 2003 to 2006 using questionnaires and analyses of cotinine in urine and benzene and formaldehyde in indoor air. About half of the 3- to 14-year-old children in Germany live in households with at least one smoker. Smoking at home is one of the most important predictors for benzene concentrations in indoor air. Cotinine concentrations in urine can be used to identify the levels of exposure to ETS. Multivariate analysis yields several relevant predictors for ETS exposure of children in Germany.